2023
DOI: 10.1021/acs.joc.2c02844
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Difunctionalization of Alkenes: Simultaneous Construction of C–Se and C–S Bonds

Abstract: Electrochemical oxidation of alkene difunctionalization with simultaneous construction of C−Se and C−S bonds is reported. The products of β-selenylethyl dithiocarbamates are obtained with CS 2 , amines, alkenes, and diphenyl diselenides in the absence of any oxidant or metal. Furthermore, the transformation is compatible with various groups. In the preliminary mechanism studies, we propose three possible pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Recently, Dong et al accomplished an electrochemical oxidation strategy to prepare β-selenylethyl dithiocarbamates from CS 2 , 107 amines, alkenes, and diphenyl diselenides without oxidant or metal (Scheme 97). 108 Aliphatic alkenes, such as cyclohexene, cyclopentene, and allylbenzene, were well tolerated in in this transformation, giving the desired products in good yields. Cyclic secondary amines including pyrrolidine and piperidine are proved to be suitable substrates.…”
Section: Dichalcogenation Of Alkenes and Alkynesmentioning
confidence: 92%
“…Recently, Dong et al accomplished an electrochemical oxidation strategy to prepare β-selenylethyl dithiocarbamates from CS 2 , 107 amines, alkenes, and diphenyl diselenides without oxidant or metal (Scheme 97). 108 Aliphatic alkenes, such as cyclohexene, cyclopentene, and allylbenzene, were well tolerated in in this transformation, giving the desired products in good yields. Cyclic secondary amines including pyrrolidine and piperidine are proved to be suitable substrates.…”
Section: Dichalcogenation Of Alkenes and Alkynesmentioning
confidence: 92%
“…In 2023, Dong's group reported a region-selective electrochemical four-component difunctional selenylation of olefins for synthesis of a series of β-selenethyldithiocarbamate products (Scheme 30). [44] It is reported that this method was compatible with both electron-withdrawing and electrondonating groups. But this reaction of CS 2 , amines, olefins, and diaryl diselenides only afforded the products with mild yields of 35-63 %.…”
Section: With Carbon Disulfide As a Sulfur Sourcementioning
confidence: 96%
“…37 An electrochemical method for the synthesis of β-selenylethyl dithiocarbamates was recently developed by Dong and Ren et al (Scheme 10). 38 This protocol employed n Bu 4 NBF 4 as the supporting electrolyte and K 2 CO 3 as a base in CH 3 CN at ambient temperature. Several control experiments were performed to gain mechanistic insights.…”
Section: Intermolecular Selenofunctionalizationmentioning
confidence: 99%